2018
DOI: 10.1038/s41467-018-05837-7
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer surface chemistry enables 2-colour single molecule localisation microscopy of adhesive ligands and adhesion proteins

Abstract: Nanofabricated and nanopatterned surfaces have revealed the sensitivity of cell adhesion to nanoscale variations in the spacing of adhesive ligands such as the tripeptide arginine-glycine-aspartic acid (RGD). To date, surface characterisation and cell adhesion are often examined in two separate experiments so that the localisation of ligands and adhesion proteins cannot be combined in the same image. Here we developed self-assembled monolayer chemistry for indium tin oxide (ITO) surfaces for single molecule lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…15a, b). We tested the functionality of RGD peptide by utilizing RGE peptide as a mutated control peptide 33 . We found that the subsequent formation of the Mg 2+ -BP NPs with RGE-BP did not significantly promote macrophage adhesion, when compared with the MgBNP dimer, thereby confirming the functionality of the RGD peptide to promote macrophage adhesion (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…15a, b). We tested the functionality of RGD peptide by utilizing RGE peptide as a mutated control peptide 33 . We found that the subsequent formation of the Mg 2+ -BP NPs with RGE-BP did not significantly promote macrophage adhesion, when compared with the MgBNP dimer, thereby confirming the functionality of the RGD peptide to promote macrophage adhesion (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As such, the early forays into single molecule microscopy methods by biosensor researchers have mostly used these methods for characterizing how biointerfaces are working at a single molecule level. 25 The knowledge obtained using these sophisticated microscopies will suggest much simpler sensor technologies to assess specific molecular functions.…”
Section: T H Imentioning
confidence: 99%
“…Secondly, surfaces that are both compatible with high‐resolution light microscopy and are electroactive are required. This typically means ITO, although studies of less common transparent materials are of interest . Of the molecules that have been shown to undergo electrochemical switching of their fluorescence, improvements are needed in photostability and fluorescence quantum yields .…”
Section: Figurementioning
confidence: 99%